2020
DOI: 10.1080/02786826.2020.1822512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combustion conditions on physical and morphological properties of biomass burning aerosol

Abstract: The study of biomass burning particle density provides information on aging, new particle formation, transport properties, and is an important parameter in aerosol impacts modeling. Density is used in mass closure techniques to estimate the temporal resolution of particulate mass concentrations. However, the study of BB particle density as a function of burning conditions is still limited. Laboratory measurement of six sub-Saharan African biomass fuels burned under a range of conditions, from pure smoldering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…In this study, the SMPS sampled from 14‐720 nm and in‐software multiple charging correction was applied. We found that ρ eff was size independent for burns with MCE < 0.9 (Pokhrel et al., 2021), so for burns with MCE < 0.9, we used the average value of ρ eff calculated from 4–6 different sizes. For burns with MCE >0.9, ρ eff shows a size dependence, with smaller values of ρ eff for larger mobility sizes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the SMPS sampled from 14‐720 nm and in‐software multiple charging correction was applied. We found that ρ eff was size independent for burns with MCE < 0.9 (Pokhrel et al., 2021), so for burns with MCE < 0.9, we used the average value of ρ eff calculated from 4–6 different sizes. For burns with MCE >0.9, ρ eff shows a size dependence, with smaller values of ρ eff for larger mobility sizes.…”
Section: Methodsmentioning
confidence: 99%
“…where C is a pre-factor and D fm is the mass mobility exponent (Park et al, 2003(Park et al, , 2004Pokhrel et al, 2021). On combining Equations 1 and 4, ρ eff can be expressed as:…”
Section: Particulate Mass Measurementmentioning
confidence: 99%
“…During the BB season (from June to October), the physical and chemical properties of BB aerosols change with variations in combustion conditions, source fuel and meteorological conditions, resulting in variations in the optical characteristics of BB aerosols (Pokhrel et al, 2021). Although satellite and surface-based sun photometer observations are able to estimate long-term SSA variation, the presence of the extensive clouds makes it difficult to retrieve SSA in the marine boundary layer in the SEA (Haywood et al, 2004;Eswaran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning organic aerosol (BBOA) is another abundant type of aerosol in the atmosphere. , In contrast to SOA, BBOA is emitted directly to the atmosphere during the combustion of vegetation, including forests and crop residues. , The chemical composition and properties of BBOA will depend on both the fuel type and the combustion conditions. Like SOA, BBOA also consists of many different organic molecules. BBOA also includes light-absorbing organic molecules, referred to as brown carbon, that can have a large positive radiative effect on the Earth–Atmosphere system. …”
Section: Introductionmentioning
confidence: 99%